Unconfined compressive strength and pore structure evolution law of structural clay after disturbance - Tang, Bin; Xie, Liang; Wang, Wei; Zhou, Biaohe; Gong, Yanxia (Frontiers in Earth Science, 2022)
The clay in the Zhanjiang Formation has thixotropic properties, which has greatly influenced the foundation engineering in the Zhanjiang area. The evolution law of macroscopic strength and clay microstructure during thixotropy can be used to explain the practical engineering problems caused by thixotropy. For undisturbed and reconstituted soil curing for a different period, unconfined compressive strength test, scanning electron microscopy, and mercury injection porosimetry test were carried out to obtain the unconfined compressive strength and pore structure evolution law in the thixotropic process. The results indicate that the Zhanjiang Formation structural clay is very sensitive to disturbance and its unconfined compressive strength decreases from 180.29 to 11.73 kPa after the natural structure is completely destructed. After 300 d of curing, the unconfined compressive strength of clay increased from 11.73 to 53.43 kPa because of thixotropy, which increased by 3.55 times. The stacking flaky flocculation structure of the undisturbed soil is destructed by reconstituting, turning to flaky flocculation structure, and the large pores are homogenized, the small pores develop into medium pores, and there is a decrease in soil strength. In the process of thixotropy, the soil particles gradually coagulate and form an aggregates flocculation structure, and the strength of clay increases with the increase in the degree of cementation. Based on the results, the thixotropic pattern of clay was established and its thixotropic mechanism was explained.